Effects of orofacial myofunctional therapy on masticatory function in individuals submitted to orthognathic surgery: a randomized trial - Daniela Galvão de Almeida Prado; Giédre Berretin-Felix; Renata Resina Migliorucci; Mariana da Rocha Salles Bueno; Raquel Rodrigues Rosa; Marcela Polizel; Isadora Ferraz Teixeira; Maria Beatriz Duarte Gavião (University of São Paulo, 2018)
Abstract Objectives: The esthetic and functional results of orthognathic surgery of severe dentofacial deformities are predictable, however there are differences regarding the effects on stomatognathic system. The aim was to investigate the effects of orofacial myofunctional therapy (OMT) on the masticatory function in individuals with dentofacial deformity submitted to orthognathic surgery (OGS). Material and Methods: Forty-eight individuals (18-40 years) were evaluated, 14 undergoing OMT (treated group-TG), 10 without this treatment (untreated group-UTG) and 24 in a control group with normal occlusion; for clinical aspects the data of an individual was missed (n=46). Chewing was performed using the Expanded protocol of orofacial myofunctional evaluation with scores (OMES-E). Muscle tone and mobility were also analyzed before (P0), three (P1) and six months (P2) after OGS. Surface electromyography of the masseter and temporalis muscles was performed, considering the parameters amplitude and duration of act and cycle, and the number of masticatory cycles. The OMT consisted of ten therapeutic sessions along the postoperative period. The results were compared using parametric and non-parametric tests. Results: TG showed higher scores in P1 and P2 than P0; for the masticatory type the scores in P2 were significantly higher than P0. In addition, the proportion of individuals with adequate tone of lower lip and adequate tongue mobility for TG increased significantly from P1 and P2 in relation to P0. The EMG results showed a decrease in act and cycle duration in P2 in relation to P0 and P1 for the TG; furthermore the values were close to controls. An increase in the number of cycles from P0 to P2 was also observed, indicating faster chewing, which may be attributed to an improvement of balanced occlusion associated with OMT. Conclusion: There were positive effects of OMT on the clinical and electromyography aspects of chewing in individual submitted to orthognathic surgery.